1991
DOI: 10.1002/eji.1830210712
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical identification of a direct physical interaction between the CD4: p56lck and Ti(TcR)/CD3 complexes

Abstract: The CD4 and CD8 antigens function in synergy with the TcR/CD3 complex in the generation of intracellular signals leading to T cell proliferation. The association of the protein-tyrosine kinase p56lck with CD4 and CD8 provides a potential mechanism in the generation of intracellular signals. Several studies have shown that CD4 can co-modulate with TcR/CD3 suggesting that these receptor complexes may associated on the surface of the T cell. Nevertheless, it has proven difficult to formally demonstrate a direct p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0

Year Published

1992
1992
1994
1994

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(42 citation statements)
references
References 46 publications
(24 reference statements)
3
39
0
Order By: Relevance
“…Although previous studies have raised controversy about the effects of HIV-1 gp120-mediated CD4 cross-linking on p56lCk activity (32,35,37), data from four experiments indicated that the cross-linking of HIV-1 gp120 has a marked modulator effect on the activity of PI 3-and PI 4-kinases associated with the receptor. DISCUSSION CD4-pS6ck associates and synergizes with the TcRUICD3 complex in the optimal response of T cells to antigen (2,8,20,59). p561ck expression is also required for thymic differentiation and the ability of T cells to respond to foreign antigen (46).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although previous studies have raised controversy about the effects of HIV-1 gp120-mediated CD4 cross-linking on p56lCk activity (32,35,37), data from four experiments indicated that the cross-linking of HIV-1 gp120 has a marked modulator effect on the activity of PI 3-and PI 4-kinases associated with the receptor. DISCUSSION CD4-pS6ck associates and synergizes with the TcRUICD3 complex in the optimal response of T cells to antigen (2,8,20,59). p561ck expression is also required for thymic differentiation and the ability of T cells to respond to foreign antigen (46).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies by us (53) have shown that the TcRC/CD3-p59'5n complex also associates with PI 3-kinase. In the context of a multimeric complex (7,8), CD4-p56lck could contribute to the overall level of PI 3-kinase activity. Alternatively, given that only a small percentage of TcRV/CD3 complexes associated with p59Yf (and hence, associated PI 3-kinase), CD4-p56lck may contribute the lipid kinase in coreceptor interactions involving TcRC/CD3-p59'5n negative complexes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous data had shown that the protein tyrosine kinases p56 lck and p59~, CD3-~, and ~" chains copurify with the accessory receptor molecules CD2, CD4, CD5, and CD8 as well as the TCR/CD3 complex in Brij lysates of rat and human T lymphocytes (24)(25)(26)(27)(28)(29). It was therefore important to investigate whether pp29/30 copurifies also with these receptors.…”
Section: Identification Of Novel Cd2-associated Phosphoproteins By Mementioning
confidence: 99%
“…Signaling is mediated by p56lck and p59fyn(T), which associate with the CD4/CD8 and TCRt/CD3 complexes, respectively (2)(3)(4)(5). CD4 and CD8 associate and functionally synergize with the TCRC/CD3 complex, augmenting T-cell proliferation (6)(7)(8). p59fyn(T), a form of p59fyn expressed in T cells, is generated by alternative splicing (9).…”
mentioning
confidence: 99%